Ferroptosis: a double-edged sword that enhances radiation sensitivity and facilitates radiation-induced injury in tumors - Liu, Yang; Zhan, Jianhao; Wang, Jisheng; Zeng, Xiaoping; Liu, Shanshan; Huang, Le; Niu, Liyan; Sun, Chengpeng; Ding, Zijun; Xing, Yan; Zhou, Zhengyu; Li, Xiaoying; et al. (Frontiers in Immunology, 2025)
Cell death is a crucial mechanism by which radiotherapy eliminates tumor cells. Ferroptosis, characterized by intracellular iron overload and lipid peroxidation, represents a distinct form of programmed cell death. Recent research has demonstrated that numerous malignant tumors exhibit high sensitivity to ferroptosis. Therefore, the induction of ferroptosis in tumor cells has emerged as a promising approach to overcome apoptosis resistance and increase sensitivity to radiotherapy. In this review, we aim to shed light on ferroptosis and its dual roles in both enhancing radiation sensitivity in tumor cells and facilitating radiation-induced injury. Then we discussed the contradiction of ferroptosis between radiation sensitivity and radiation-induced injury, providing valuable insights and directions for the advancement of clinical tumor radiotherapy.